Postoperative outcome after oesophagectomy for cancer: Nutritional status is the missing ring in the current prognostic scores. Issue 6 (June 2015) - Filip, B.; Scarpa, M.; Cavallin, F.; Cagol, M.; Alfieri, R.; Saadeh, L.; Ancona, E.; Castoro, C.
Abstract Background Several prognostic scores were designed in order to estimate the risk of postoperative adverse events. None of them includes a component directly associated to the nutritional status. The aims of the study were the evaluation of performance of risk-adjusted models for early outcomes after oesophagectomy and to develop a score for severe complication prediction with special consideration regarding nutritional status. Methods A comparison of POSSUM and Charlson score and their derivates, ASA, Lagarde score and nutritional index (PNI) was performed on 167 patients undergoing oesophagectomy for cancer. A logistic regression model was also estimated to obtain a new prognostic score for severe morbidity prediction. Results Overall morbidity was 35.3% (59 cases), severe complications (grade III–V of Clavien–Dindo classification) occurred in 20 cases. Discrimination was poor for all the scores. Multivariable analysis identified pulse, connective tissue disease, PNI and potassium as independent predictors of severe morbidity. This model showed good discrimination and calibration. Internal validation using standard bootstrapping techniques confirmed the good performance. Conclusions Nutrition could be an independent risk factor for major complications and a nutritional status coefficient could be included in current prognostic scores to improve risk estimation of major postoperative complications after oesophagectomy for cancer.